2020
DOI: 10.1002/rcr2.553
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral pulmonary hamartoma with haemoptysis from the non‐adjacent bronchus

Abstract: We report a rare case of peripheral pulmonary hamartoma that caused haemoptysis from the non‐adjacent bronchus. A 54‐year‐old man was admitted to our hospital because of haemoptysis. Contrast‐enhanced chest computed tomography revealed a tumour measuring 25 × 24 mm in the left lower lobe. Fluid was observed around the pulmonary artery in addition to the consolidation of the lingular segment of the left lung. Bronchoscopy confirmed continuous bleeding from the lingular bronchus, and surgery was planned. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Hamartomas are one of the most common benign pulmonary tumors [ 11 ]. Hamartoma comprises cartilage, connective tissue, muscle, fat, and bone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hamartomas are one of the most common benign pulmonary tumors [ 11 ]. Hamartoma comprises cartilage, connective tissue, muscle, fat, and bone [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is rare, hamartoma can also cause hemoptysis [ 6 ]. Kitamura et al reported hemoptysis from non-adjacent bronchus in peripheral pulmonary hamartoma [ 11 ]. Active TB can also have hemoptysis presentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation